MANAJEMEN KRISIS PUBLIC RELATIONS POLDA JABAR DALAM MEMBANGUN CITRA POSITIF MELALUI MEDIA MASSA - Shofya Sartikasari Widhara (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
West Java Police experienced a crisis due to cases of police abuse of his own stepson. Crisis management is an effort taken in facing a crisis while trying to prevent the widespread impact of a crisis event with the aim of regaining public trust. In crisis situations, the role of Public Relations becomes very important because they must have the ability to maintain the company's reputation when facing challenges from the public. This study aims to determine the extent of crisis management public relations (PR) applied by the West Java Regional Police in building a positive image through the mass media. Researchers used crisis management theory from Coombs & Holladay with three subanalysis, namely pre-crisis, crisis, and post-crisis in analyzing the crisis management of West Java Regional Police PR. The method used by the researcher is qualitative with PR case study approach. The results showed the identification of the crisis carried out with the Coordination of the Cirebon police and the investigation by the PROPAM, West Java Police Public Relations also conducted news monitoring through the mass media, crisis analysis by analyzing the perpetrators and also conducting a visa for victims, followed by providing an explanation to the media in a transparent manner and carrying out the role of the mass media during the crisis, then at the last stage, namely by conducting positive activities, building relationships and good relations and always updating positive activities. With the crisis management stage carried out by the West Java Regional Police Public Relations, the case of police misconduct against her stepdaughter can be resolved properly. Keywords: crisis management, mass media, positive image, public relations